THE INFLUENCE OF CURRENT RATIO, DEBT TO EQUITY RATIO, NET PROFIT MARGIN, AND SALES GROWTH ON FINANCIAL DISTRESS CONDITIONS - Nur Aini Tri Amanah; Baniady Gennody Pronosokodewo; Ratna Pumama Sari (Count : Journal of Accounting, Business and Management, 2023)
The transportation sector in Indonesia is one of the most important sectors that determines the level of competitive advantage of the Indonesian economy. Companies that experience a decrease in revenue can threaten the survival of the company, resulting in financial distress (financial distress). This study aims to determine the Current Ratio, Debt to Equity Ratio, Net Profit Margin, and Sales Growth in influencing financial distress in transportation companies in Indonesia. This study used a purposive sampling method which produced a sample according to the criteria, namely 12 transportation companies. The analysis used is logistic regression analysis with SPSS statistical tools. The results of the hypothesis test show that the Current Ratio has a significant negative effect on financial distress, while the Debt to Equity Ratio, Net Profit Margin, and Sales Growth have no effect on financial distress.